Castle Lite - Ron Irwin (Communicare)
One of South Africa’s most successful recent branding initiatives is the rebranding and repositioning of SABMiller’s Castle Lite beer. Light beer branding has a long and successful history in the United States, where brand names like Bud Light have long held a significant market share. However, sales of Castle Lite were low, leading into 2009. SABMiller’s approach to bolster sales was to build a narrative around the brand that moved away from the concept of ‘light’, or ‘low calorie’, or even ‘low alcohol’ and reframe the consumer perception of this beer around the symbolic value of ‘Extra Cold Refreshment’. This article examines the means through which Castle Lite consumers were invited to form a unique, imagined community of beer drinkers through a number of media formats. It offers advertisers, academics and brand managers a concise case study that illustrates how a failing brand can be relatively quickly repositioned to dramatically increase market penetration, consumer brand knowledge and overall sales.